Dinâmica da água do solo em cultivos agrícolas sob a influência de resíduos culturais e os impactos na produtividade de plantas - Dantas, Max Kleber Laurentino (2020)
The presence of vegetable residues on the soil surface is one of the main components that influence the soil water balance, once it acts directly in the water evaporation process of the system. With the scarcity of water resources in recent years, there has been a significant increase in irrigated areas. This phenomenon resulted in the necessity to use techniques that increase the efficiency of water use, associated with conservationist practices of the soil. Thus, the objective of this study was to analyze the dynamics of water losses in soil with the presence of vegetable residues in comparison to a bare soil. Furthermore, it was intended to analyze the effects of the practice of deficient irrigation associated with the presence of vegetable residues in a soil cultivated with sunflower, analyzing its effects on plant growth and development. The work was divided into two studies, both performed in the experimental area of Sistema Irriga®, Rural Engineering Department, Federal University of Santa Maria (UFSM). Study I was conducted in the harvest 2017/18, in a mobile cover “Rainout Shelter” in soil cultivated with soybean. The experimental design used was completely randomized (DIC), bifactorial, with four replications. Factor A consisted of two levels of residues and bare soil and factor B, due to the presence and absence of cultivated plants. The soil water content was monitored by FDR sensors and the water balance was performed based on the variation in water storage in the soil. The direct soil water evaporation was measured using microlysimeters. After each irrigation event, the water retained in the plant residues was quantified by lysimetry. Weekly, determinations were made to evaluate the plants growth and development and, at the end of the cycle, the crop yield components were determined. Study II was conducted in the harvest 2018/19, in a completely randomized design (CRD), bifactorial, with three replications. Factor A was constituted by different levels of deficient irrigation, based on 80 (T80), 70 (T70), 60 (T60) and 50% (T50) of the soil total available water (TAW), in a soil cultivated with sunflower. Irrigations were performed when the soil water content reached the pre-defined percentages for each treatment. Factor B was constituted by the presence and absence of vegetable residues disposed on the soil surface. In this work, soil water dynamics, crop yield components, content and components of vegetable oil present in seeds and nutrient accumulation in dry plant biomass were evaluated. The results showed that the fraction of water retained in vegetable residues is directly dependent on its quantity. In addition, under the conditions of this study, there was a maximum retention of approximately 10% of the water applied via sprinkler irrigation, when 100% of residues were maintained on the surface. The practice of deficient irrigation proved to be an efficient alternative to reduce water consumption without affecting sunflower growth and development. The presence of residues was a factor that contributed to the application of this practice, since the soil water content was maintained even with the increase in the deficit irrigation level.